2017
DOI: 10.2527/jas.2016.0789
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of Lactobacillus plantarum JM113 in vitro and its protective effect on broiler chickens challenged with deoxynivalenol1

Abstract: The aim of this experiment was to study the antioxidant capacity of JM113 isolated from healthy intestinal contents of Tibetan chicken and its protective effect on broiler chickens challenged with deoxynivalenol (DON). Compared with PZ01 and M23, JM113 demonstrated maximum reducing ( < 0.05) activity and resistance in the presence of 1.2 mmol/L hydrogen peroxide, and great scavenging ability ( < 0.05) against hydroxyl, superoxide anion, and 1,1-diphenyl-2-picrylhydrazyl radicals in vitro. For each strain, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 48 publications
4
36
0
Order By: Relevance
“…Exposure of CFS of two L. plantarum strains in combination with DON significantly prevented these toxic effects on intestinal mucosa layers in piglets. Apart from these studies, various effects of LAB strains in ameliorating DON‐related toxigenic effects have been reported in ex vivo studies conducted on animals (Wan, Turner, Allen, & El‐Nezami, ; Yang, Li, Duan, & Yang, ). In a recent study (Wu et al., ), DON‐related intestinal toxicity in broiler chickens was found to be related to changes in intestinal morphology, particular jejunum and duodenum, that included shortening of villi and deepening of crypts.…”
Section: Protection Provided By Lab Against the Toxic Effects Of Mycomentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of CFS of two L. plantarum strains in combination with DON significantly prevented these toxic effects on intestinal mucosa layers in piglets. Apart from these studies, various effects of LAB strains in ameliorating DON‐related toxigenic effects have been reported in ex vivo studies conducted on animals (Wan, Turner, Allen, & El‐Nezami, ; Yang, Li, Duan, & Yang, ). In a recent study (Wu et al., ), DON‐related intestinal toxicity in broiler chickens was found to be related to changes in intestinal morphology, particular jejunum and duodenum, that included shortening of villi and deepening of crypts.…”
Section: Protection Provided By Lab Against the Toxic Effects Of Mycomentioning
confidence: 99%
“…The use of LAB strains with antioxidative effects has proved to be an effective approach to combat with DON-caused oxidative stress. For instance, Yang, Li et al (2017) demonstrated the amelioration of DON-based oxidative intestinal damage of broiler chickens by L. plantarum strain JM113 with a well-characterized anti-oxidant activity. There are many LAB strains that have been reported to have antioxidant activity (Amaretti et al, 2013;Li et al, 2012) and thus such strains are ideal supplements for the alleviation of oxidative stress caused by DON and many other mycotoxins.…”
Section: Protection Against Donmentioning
confidence: 99%
“…In comparison, Lactobacillus is considered to be a good candidate since it can improve intestinal health by stimulating the immune system, modulating gut microbiota, and preventing oxidative damage [ 22 ], thereby eliminating the hazards of DON. The Lactobacillus plantarum ( L. plantarum ) JM113 strain has high antioxidant activity and thereby supplementation in feed has the potential to protect the integrity of the intestinal barrier in broilers challenged with DON [ 22 ]. This study was carried out to evaluate the beneficial effects of L. plantarum JM113 on the intestinal toxicity of DON in broilers.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma antioxidant system is an important part of a broiler's antioxidant system, which plays an important role in enhancing anti-stress ability (24) . And T-AOC, GSH-Px and superoxide dismutase activities and malondialdehyde content are usually used as indicators for measuring plasma antioxidant capacity (25,26) . To the best of our knowledge, there have been few studies on the effect of IOF of vitamin C on plasma antioxidant capacity of broilers.…”
Section: Discussionmentioning
confidence: 99%